Texture and mechanical properties of single crystal copper during equal channel angular pressing by route C: Struktur und mechanische Eigenschaften von monokristallinem Kupfer durch ECAP‐Umformen nach Variante C. Issue 10 (1st October 2018) - Guo, T.B.; Li, Q.; Wang, C.; Jia, Z.; Hu, Y.; Tang, X.C.
Abstract: Single crystal copper has excellent electrical and thermal conductivity, but the lower strength seriously limited its application. Traditional strengthening methods, such as alloying, will severely damage its conductivity. Severe plastic deformation is the most effective methods for increasing the metals strength and not reducing the conductivity. The microstructure and texture evolution of single crystal copper (99.999 %) during equal channel angular pressing by route C was investigated by scanning electron microscopy, X‐ray diffraction, electron backscatter diffraction and transmission electron microscopy, the mechanical properties and conductivity were tested, and the influence mechanism of texture and microstructure on mechanical properties and conductivity were analyzed. The results show that during equal channel angular pressing, the original <111> orientation gradually changed to <001>, accompany lots of low‐angle grain boundaries were formed. With strain increasing, the high‐angle grain boundaries increased gradually, and the deformation bands with <110> orientation was formed in the single crystal structure, which plays a positive role on the conductivity. After 5 passes, the tensile strength of single crystal copper increased from 168 MPa to 415 MPa by route A and 385 MPa by route C, and the elongation declined sharply from 63 % to 30 % and 27.9 %, respectively. After 16 passes, the hardness increased from 60.4 HV to 130.8 HV and the conductivity only slightly down.